2017
DOI: 10.18632/oncotarget.17716
|View full text |Cite
|
Sign up to set email alerts
|

Differences in risk factors of malignancy between men and women with type 2 diabetes: A retrospective case-control study

Abstract: BackgroundThe aim of this multicenter, retrospective, case-control study was to identify differences in risk factors of malignancy between men and women with type 2 diabetes.ResultsAmong women the most prevalent malignancies were: breast and uterine cancers (35.6% and 14.4% respectively), while among men there were: colorectal and prostate cancers (24.5% and 13.3% respectively). In both gender metformin use was associated with lower cancer risk. Obesity and insulin treatment in dose-dependent and time-varying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The first clinical reports indicating the protective effect of metformin in terms of cancer incidence and cancer death risk appeared in the middle of the first decade of this century [72,73]. Own studies also confirmed protective effect of metformin in the Polish population, irrespective of gender [74,75]. In numerous meta-analyses of case-control and cohort studies, metformin use was associated with 10-40% reduction of cancer incidence and mortality, which was summarized by Heckman-Stoddard et al in their paper [76].…”
Section: Metforminmentioning
confidence: 90%
See 1 more Smart Citation
“…The first clinical reports indicating the protective effect of metformin in terms of cancer incidence and cancer death risk appeared in the middle of the first decade of this century [72,73]. Own studies also confirmed protective effect of metformin in the Polish population, irrespective of gender [74,75]. In numerous meta-analyses of case-control and cohort studies, metformin use was associated with 10-40% reduction of cancer incidence and mortality, which was summarized by Heckman-Stoddard et al in their paper [76].…”
Section: Metforminmentioning
confidence: 90%
“…The first observational studies seemed to confirm this relationship [ 72 , 73 , 86 ], although there were differences between individual formulations [ 87 ]. Own observation, as well as the largest systematic review, did not show an increased risk of cancer associated with the use vs. non-use of sulfonylureas [ 74 , 75 , 88 ].…”
Section: Antidiabetic Medications and Cancermentioning
confidence: 99%
“…Previous studies indicated that there are significant differences of cardiovascular disease incidence in gender and age. [17][18][19] Estrogen protection against NRVHD may contribute to a lower risk in NRVHD in premenopausal women than age-matched men. 20 This study also assessed the risk factors of NRVHD.…”
Section: Discussionmentioning
confidence: 99%
“…The incident cases in any year were higher for females than for males; in 2019, they were 0.90 million (95% UI = 0.85 to 0.95 million), respectively, for females, and 0.76 million (95% UI = 0.70 to 0.81 million) for males. The age-standardized incidence rate (ASIR) increased slightly from 1990 to 2019 (EAPC = 0.39, 95% UI = 0.29 to 0.49), being 18 The ASIR in any year was also higher for females than for males.…”
Section: Global and Regional Incidence Of Non-rheumatic Valvular Hear...mentioning
confidence: 99%